Imaging system design based on electromagnetic tomography for high conductivity medium reconstruction - Liu, Xianglong; Wang, Ying; Li, Danyang (Review of scientific instruments, 2023)
Electromagnetic tomography (EMT) is used to create tomographic images of the electrical properties of conducting material based on electromagnetic measurements from coils evenly distributed around the imaging region. EMT is widely used in industrial and biomedical fields for which it offers the advantages of being non-contact, fast, and non-radiative. Most EMT measurement systems are implemented with commercial instruments, such as impedance analyzers and lock-in amplifiers, which are bulky and inconvenient for portable detection devices. In order to improve the portability and extensibility, a purpose-built flexible and modularized EMT system is presented in this paper. The hardware system consists of six parts: the sensor array, signal conditioning module, lower computer module, data acquisition module, excitation signal module, and the upper computer. The complexity of the EMT system is reduced by a modularized design. The sensitivity matrix is calculated by the perturbation method. The split Bregman algorithm is applied to solve the L1 norm regularization problem. The effectiveness and advantages of the proposed method are verified by numerical simulations. The average signal to noise ratio of the EMT system is 48 dB. Experimental results verified that the reconstructed images can show the number and positions of the imaging objects, demonstrating the feasibility and effectiveness of the novel imaging system design.